EVALUASI PEMILIHAN SUPPLIER KAYU MENGGUNAKAN METODE WEIGHTED PRODUCT DAN TOPSIS PADA CV BELA SEJAHTERA - Riko Serpus; Audley Kelvin Alexander; Cindy Malinda Uscha; Dewi hajar (MEDIANTARA: Indonesian Journal of Creative Business and Technology (IJCBT), 2026)
Selecting the right wood Supplier is a critical factor in ensuring smooth production processes and maintaining the quality of raw materials used by a company. Mistakes in Supplier selection can lead to production delays, increased costs, and a decline in final product quality. Therefore, this study aims to determine the best wood Supplier using a Multi-Criteria Decision Making (MCDM) approach. This research employs a descriptive quantitative approach involving four alternative Suppliers and seven evaluation criteria: wood price, wood quality, delivery punctuality, Supplier distance, supply capacity, payment system, and Supplier reputation. Data were collected through structured interviews with company decision makers and a review of relevant internal documents. The analytical methods used are Weighted Product (WP) and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) to rank Suppliers based on the established criteria. The results indicate a difference in Supplier rankings between the two methods due to differing calculation approaches and evaluation concepts. The WP method emphasizes the consistency of Supplier performance across all criteria, while the TOPSIS method assesses the proximity of an alternative to the ideal solution. Based on the analysis, the Weighted Product method is considered more appropriate and is recommended for determining the best wood Supplier for the company.